The Determinant Factors of KAI Access Awareness in PT Kereta Api Indonesia from Millennial Generation Perspective - Rano Kartono; Afif Wildan Tamami (Bina Nusantara University, 2020)
PT Kereta Api Indonesia (Persero), as a monopoly train company in Indonesia, launches KAI Access which has been downloaded by more than 5 million users, but only about 1,1 million users are active. The research intended to determine the relationship between brand experience, brand trust, perceived quality of customer satisfaction, and brand awareness in the minds of KAI Access consumers. The research used primary data with millennial populations by 986.775 and purposive sampling method with 400 KAI Access users spread over 9 Daops (operational areas) of PT Kereta Api Indonesia in Java with a Partial Least Square (PLS) analysis approach. The results show that brand experience and perceived quality have a positive effect on customer satisfaction while brand trust has a negative effect. Whereas customer satisfaction and brand experience are directly proportional to brand awareness.